Development of an Artificial Vision System for Underwater Vehicles - Cristian Méndez Sanmartín; Moisés Bautista Briceño (Proceedings, 2019)
Beyond certain depth there is no light, supposing the main obstacle in the use of optical systems beneath the water. Therefore, the underwater vision system developed is composed of a set of underwater lights which allow the system to work properly and the cameras. These are integrated with the navigation system through the Robot Operating System (ROS) framework, which handles the acquisition and processing of information to be used as support for the navigation and which is also essential for its use in reconnaissance missions.